Rationalistic Model of Land Bank Institutional Regulation in PERPU No. 2 of 2022 Concerning Job Creation in Harmony with the Principle of Legal Benefits - Yusna Wulan Sari Tanjung; Binsar Jon Vic (Indonesian Journal Publisher, 2026)
This study examines the rationale for establishing the Land Bank Institution under Government Regulation in Lieu of Law (Perppu) No. 2 of 2022 concerning Job Creation. Land acquisition for public purposes in Indonesia has long faced challenges due to population growth, increasing land prices, limited land availability, and disputes over compensation. To address these issues, the government introduced the Land Bank as part of its agrarian reform agenda under the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. The Land Bank is intended to ensure land availability for public interests, social welfare, national development, economic equity, land consolidation, and agrarian reform. Its establishment is expected to improve the efficiency of land acquisition processes and reduce conflicts related to compensation payments. However, because the Land Bank was not previously regulated under Law No. 5 of 1960 concerning Basic Agrarian Principles, its creation has raised questions regarding its legal basis, implementation, and effectiveness in serving community interests. This research employs a normative juridical method with a statutory approach, utilizing primary and secondary legal sources. The study finds that the Land Bank is designed to support legal certainty and public welfare by providing a structured mechanism for land management and acquisition. Furthermore, public dissemination and understanding of the Land Bank framework are essential to ensure that its implementation aligns with the principle of legal benefit and contributes to resolving land-related problems in Indonesia.